Design and Synthesis of New Quinoxaline Derivatives as Potential Histone Deacetylase Inhibitors Targeting Hepatocellular Carcinoma: In Silico, In Vitro, and SAR Studies - Ma, Chao; Taghour, Mohammed S.; Belal, Amany; Mehany, Ahmed B. M.; Mostafa, Naglaa; Nabeeh, Ahmed; Eissa, Ibrahim H.; Al-Karmalawy, Ahmed A. (Frontiers in Chemistry, 2021)
Guided by the structural optimization principle and the promising anticancer effect of the quinoxaline nucleus, a new series of novel HDAC inhibitors were designed and synthesized. The synthesized compounds were designed to bear the reported pharmacophoric features of the HDAC inhibitors in addition to an extra moiety to occupy the non-used vacant deep pocket of the HDAC receptor. The newly prepared compounds were evaluated for their in vitro anti-proliferative activities against HepG-2 and HuH-7 liver cancer cell lines. The tested compounds showed promising anti-proliferative activities against both cell lines. The most active ten candidates (6c, 6d, 6f, 6g, 6k, 6l, 7b, 8, 10h, and 12) were further evaluated for their effect on the gene expression levels of Bax as an apoptotic marker and Bcl-2 as an anti-apoptotic one. Moreover, they were evaluated for their ability to inhibit histone deacetylase (HDAC1, HDAC4, and HDAC6) activities. Compound 6c achieved the best cytotoxic activities on both HepG-2 and HuH-7 cell lines with IC50 values of 1.53 and 3.06 µM, respectively, and also it showed the most inhibitory activities on HDAC1, HDAC4, and HDAC6 with IC50 values of 1.76, 1.39, and 3.46 µM, respectively, compared to suberoylanilide hydroxamic acid (SAHA) as a reference drug (IC50 = 0.86, 0.97, and 0.93 µM, respectively). Furthermore, it achieved a more characteristic arrest in the growth of cell population of HepG-2 at both G0/G1 and S phases with 1.23-, and 1.18-fold, respectively, compared to that of the control, as determined by cell cycle analysis. Also, compound 6c showed a marked elevation in the AnxV-FITC apoptotic HepG-2 cells percentage in both early and late phases increasing the total apoptosis percentage by 9.98-, and 10.81-fold, respectively, compared to the control. Furthermore, docking studies were carried out to identify the proposed binding mode of the synthesized compounds towards the prospective target (HDAC4). In silico ADMET and toxicity studies revealed that most of the synthesized compounds have accepted profiles of drug-likeness with low toxicity. Finally, an interesting SAR analysis was concluded to help the future design of more potent HDACIs in the future by medicinal chemists.